Detection of renal scars by transplant renal ultrasounds and DMSA scans after urinary tract infections in paediatric renal transplant recipients. (4th April 2011) - Singh, C; Shah, S; Fernando, R; Anderson, P J; Biassoni, L; Marks, S D
Abstract : Aims: To study the clinical features and compare the accuracy of transplant renal ultrasound (TRUS) and dimercaptosuccinic acid (DMSA) scans in the detection of scars following urinary tract infection (UTI) in paediatric renal transplant recipients (RTR). Methods: Clinical notes of RTR who underwent TRUS and DMSA following UTI were reviewed for presence of bladder dysfunction, clinical presentation and episodes of culture positive UTI. The presence or absence of cortical thinning on TRUS and the severity of scarring (focal or multiple) detected on DMSA was noted. Results: 38 RTR, (21 (55%) males) aged 1.5 to 16.3 (median 5.9) years were recruited with 22 (58%) patients, with bladder abnormalities (including structural, functional, augmentation with or without need for clean intermittent catheterisation). Antibiotic prophylaxis was administered to 20 (53%) RTR for PCP prophylaxis, hostile bladders or previous history of UTI. 10 (26%) patients required hospital admission for intravenous antibiotics with 28 (74%) culture positive UTI with single or multiple pathogens. Only 10 (26%) patients had afebrile UTI and 60% of these had hostile bladders who had statistically higher incidence of renal scarring (16 (72%) vs 9 (56%) normal bladders; p=0.04). TRUS were performed in all children during or after UTI episode with 3 (8%) with renal scarring. Abnormal DMSA scans were noted in 25 (66%) patients, of whom 16 (64%) had multiple and 9 (36%) had focal defects. TRUS could delineate only 3 (12%) of the 25 patients who had a defect on DMSA. DMSA is considered the gold standard in detecting renal scarring and the calculated sensitivity of TRUS in this study was only 12%. Conclusion: UTI commonly occur in paediatric RTR with hostile bladders. The clinical features are diverse and a high index of suspicion should be maintained in order to ensure prompt treatment of UTI in RTR to prevent transplant renal scarring and preserve renal allograft function. TRUS is easily available but has a low sensitivity when compared to DMSA scans in detecting areas of scarring in transplant kidneys in paediatric RTR following UTI.